FEATURES OF REFLECTION OF MODERN MANAGEMENT ASPECTS IN MANAGEMENT DECISION-MAKING - Nazarov Azamat Sottarovich (Western European Studies, 2024)
The article defines the subject area and characterizes the sociology and psychology of management. The principles of personnel management are considered from the point of view of administrative, organizational and socio-psychological impact on personnel. Sociopsychological aspects, functions and mechanisms of management are determined. Recommendations for the effective application of socio-psychological management methods have been developed.
Keywords: psychology of management; sociology of management; humanization